Expanding Clinical Phenotype of TRAPPC12-Related Childhood Encephalopathy: Two Cases and Review of Literature - Aslanger, Ayca Dilruba; Demiral, Emine; Sonmez-Sahin, Seyma; Guler, Serhat; Goncu, Beyza; Yucesan, Emrah; Iscan, Akın; Saltik, Sema; Yesil, Gozde (Neuropediatrics, 2020)
Biallelic mutations in the TRAPPC12 gene are responsible for early-onset progressive encephalopathy with brain atrophy and spasticity (PEBAS). To date, three different allelic variants have been reported. Next-generation sequencing allowed discovery of unique alternations in this gene with different phenotypes. We report two patients carrying TRAPPC12 variants, one previously reported and one unknown mutation, with severe neurodevelopmental delay and brain atrophy. Standard clinical examination and cranial imaging studies were performed in these two unrelated patients. In addition, whole-exome sequencing was performed, followed by Sanger sequencing for verification. The first patient, a 2-year-old boy, was found to be homozygous for the previously reported c.1880C > T (p.Ala627Val) mutation. He presented with a phenotype including severe progressive cortical atrophy, moderate cerebellar atrophy, epilepsy, and microcephaly, very similar to the previously reported cases. The second case, a 9-year-old boy, carried a novel homozygous c.679T > G (p.Phe227Val) variant and presented with mild cortical atrophy, severe cerebellar atrophy, and neither clinically manifest epilepsy nor microcephaly, which were previously considered typical findings in PEBAS with TRAPPC12 mutations. Our findings suggest that clinical and brain imaging findings might be more variable than previously anticipated; however, a larger number of observations would benefit for broader phenotypic spectrum.
Keywords: brain atrophy; cerebellar atrophy; microcephaly; TRAPPopathies; TRAPPC12 mutation